2013
DOI: 10.1038/hr.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Celiprolol reduces oxidative stress and attenuates left ventricular remodeling induced by hypoxic stress in mice

Abstract: We have previously reported that intermittent hypoxic stress, which is relevant to sleep apnea syndrome (SAS), increases oxidative stress and induces left ventricular (LV) remodeling. Celiprolol, a β1-selective adrenoreceptor blocker, is known to have not only an antihypertensive effect but also an antioxidant effect through releasing nitric oxide. The aim of this study was to examine the hypothesis that celiprolol might ameliorate the LV remodeling induced by intermittent hypoxia through its antioxidant effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…It has been known that IH increases the levels of various inflammatory factors (Li et al, 2011) and we have reported that the serum levels of TNF-α and IL-6, as well as the phosphorylation of NF-κB were increased (Nishioka et al, 2013;Matsumoto et al, 2009;Yamashita et al, 2007). Increased levels of TNF-α and oxidative stress might promote the activation of NF-κB and the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…It has been known that IH increases the levels of various inflammatory factors (Li et al, 2011) and we have reported that the serum levels of TNF-α and IL-6, as well as the phosphorylation of NF-κB were increased (Nishioka et al, 2013;Matsumoto et al, 2009;Yamashita et al, 2007). Increased levels of TNF-α and oxidative stress might promote the activation of NF-κB and the development of cardiac hypertrophy.…”
Section: Discussionmentioning
confidence: 87%
“…It is known that the prevalence of sleep-related breathing disorders is high in patients with cardiovascular disease and obstructive sleep apnea is common in obese patients with atherosclerosis (Gottlieb et al, 2010). Recently, sleep apnea syndrome has been recognized as an independent risk factor of cardiovascular events, and it has been reported that intermittent hypoxia due to sleep apnea might accelerate cardiac remodeling (Nishioka et al, 2013;Kato R et al, 2014). Although reducing the LDL-cholesterol level may decrease cardiovascular events, there are still residual risks including the complication of sleep apnea syndrome (Kubo et al, 2003;Baigent et al, 2005;Gottlieb et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Rodent models of long-term intermittent hypoxia have demonstrated hypertension and increased sympathetic activity (22), increased right ventricular systolic pressure, right ventricular mass, neovascularization of distal pulmonary vessels (23), systemic and pulmonary vascular pressure (24,25), cardiac hypertrophy, and cardiac and perivascular fibrosis (26). Previous studies in children have however not found a strong link between arterial desaturation and elevated HR and BP (27).…”
Section: Repetitive Respiratory Events In Childrenmentioning
confidence: 91%
“…The outcomes observed by different authors are highly varied and likely depend on the particular IH parameters employed, such as duration, frequency, and severity of hypoxia. With consideration of these factors, long-term IH exposures in murine models showed increased right ventricular systolic pressure, right ventricular mass, neovascularization of distal pulmonary vessels (54), cardiomyocyte diameter (133), systemic and pulmonary vascular pressures (24, 132), interstitial space (33), cardiac hypertrophy, cardiac and perivascular fibrosis (133), inflammation and dysfunction (198), and a decrease in endothelial nitric oxide synthase (eNOS) expression in ventricular and aortic tissues (133,192).…”
Section: Maladaptation To Ih: Pathological Effectsmentioning
confidence: 99%